The Search for Identity of a Woman between Third World and First World in Mukherjee's Jasmine - KAYA, ONUR (Journal of History Culture and Art Research, 2015)
THE SEARCH FOR IDENTITY OF A WOMAN BETWEEN “THIRD WORLD” AND “FIRST WORLD” IN MUKHERJEE’S JASMINE Abstract The physical and psychological journey of a person is an ongoing trip. Throughout this journey, the individual develops and searches for his/her identity. From this perspective, countries like USA have many people who experience physical and pyschological journeys due to their immigrational past. Such is the case of Jasmine, the woman character in Bharati Mukherjee’s novel Jasmine (1989) who has this kind of past and searches for her identity which is stuck between the “third world” where her journey begins and the “first world” where her journey takes her. Therefore, this article aims at reveal the physical and pyschological journey of a woman who moves from a so - called “third world” country to America, the importance of her ethnicity in this journey and her struggle to search her identity in her in between situation. Firstly, due to the postcolonial background of the character, postcolonialism and its literary qualities will be emphasized as the theoretical background of the novel. In addition, ethnicity and identity theories will be further detailed upon and socio-economic conditions of the country Jasmine moves from will be explained in order to reveal the situation of the women there. Within the light of all this information, the article will focus upon a number of of specific topics such as: representations of the “third world”, America, women’s the struggle to survive, their ethnicity and search for identity.